Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jib.596
|View full text |Cite
|
Sign up to set email alerts
|

Mashbill and barrel aging effects on the sensory and chemometric profiles of American whiskeys

Abstract: American whiskeys are economically and culturally significant beverages with complex sensory profiles; however, how aromas and flavours are linked to mashbill (fermentedwash recipe) and/or aging time in new, charred oak barrels have not been thoroughly investigated. To accomplish this goal, sensory Descriptive Analysis and Chemometric analyses, including Headspace Solid-Phase Microextraction-Gas Chromatography-Mass Spectrometry and Liquid Chromatography-Quadrupole-Time-of-Flight-Mass Spectrometry, were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While baseline quality considerations present straightforward breeding targets, breeding for flavor remains at an early stage, but could benefit from advances in metabolomic profiling for spirits and sensory analysis. Phetxumphou et al (2020) have shown that both metabolomics and panelists can distinguish between high and low rye content, but to the best of our knowledge, there are no published scientific manuscripts of distillates from different rye varieties. However, at least one distillery has assessed produced estate grown rye whiskeys sourced from 14 individual rye varieties with distinct tasting notes (Far North Spirits, 2020.…”
Section: Distillation Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…While baseline quality considerations present straightforward breeding targets, breeding for flavor remains at an early stage, but could benefit from advances in metabolomic profiling for spirits and sensory analysis. Phetxumphou et al (2020) have shown that both metabolomics and panelists can distinguish between high and low rye content, but to the best of our knowledge, there are no published scientific manuscripts of distillates from different rye varieties. However, at least one distillery has assessed produced estate grown rye whiskeys sourced from 14 individual rye varieties with distinct tasting notes (Far North Spirits, 2020.…”
Section: Distillation Qualitymentioning
confidence: 99%
“…In a study involving US rye whiskeys, Lahne et al (2019) trained a sensory panel with 18 aromas and two tastes (bitter and sweet), where vanilla/oak, raw wood/cedar, floral/violet, banana, and plum/cherry were highly cited aromas. Further work by Phetxumphou et al (2020) included 21 aroma and five flavor descriptors, of which "rye" itself was a new addition to the aromatic descriptors. In their study, significant attributes changed with aging time but generally included vanilla (flavor and aroma) and cherry and bread aromas.…”
Section: Crop Sciencementioning
confidence: 99%
See 3 more Smart Citations